The Origin of a New Sex Chromosome by Introgression between Two Stickleback Fishes. (1st October 2018) - Dixon, Groves; Kitano, Jun; Kirkpatrick, Mark
Abstract: Introgression is increasingly recognized as a source of genetic diversity that fuels adaptation. Its role in the evolution of sex chromosomes, however, is not well known. Here, we confirm the hypothesis that the Y chromosome in the ninespine stickleback, Pungitius pungitius, was established by introgression from the Amur stickleback, P. sinensis . Using whole genome resequencing, we identified a large region of Chr 12 in P. pungitius that is diverged between males and females. Within but not outside of this region, several lines of evidence show that the Y chromosome of P. pungitius shares a most recent common ancestor not with the X chromosome, but with the homologous chromosome in P. sinensis . Accumulation of repetitive elements and gene expression changes on the new Y are consistent with a young sex chromosome in early stages of degeneration, but other hallmarks of Y chromosomes have not yet appeared. Our findings indicate that porous species boundaries can trigger rapid sex chromosome evolution.